Women working on a flower craft - Unknown:::Creator::::::::::::
Photograph shows a woman sitting at a table wrapping the wire stem of an artificial flower with floral tape. Two young girls are standing behind her watching. A finished flower lays on the table and a "YWCA" banner hangs on the wall behind them.